Worth it your life, your money, your terms - Steinberg, Amanda (North Star Way, 2017)
The founder of the DailyWorth.com financial site explains how women can reevaluate money as a source of personal power in order to live life on their own terms, explaining how to implement strategies for security, confidence, and management